Sarcopenia Is an Important Prognostic Factor in Patients With Cervical Cancer Undergoing Concurrent Chemoradiotherapy. Issue 1 (1st January 2018) - Kiyotoki, Takanori; Nakamura, Keiichiro; Haraga, Junko; Omichi, Chiaki; Ida, Naoyuki; Saijo, Masayuki; Nishida, Takeshi; Kusumoto, Tomoyuki; Masuyama, Hisashi
Abstract : Objective: This study aimed to investigate the correlation of sarcopenia findings with prognostic factors in patients with cervical cancer (CC) undergoing concurrent chemoradiotherapy (CCRT). Methods: We retrospectively collected data on body composition and clinicopathological features from the medical records of 60 patients with CC who underwent CCRT and analyzed correlations between prognosis and changes in body composition as measured by computed tomography (skeletal muscle and iliopsoas muscle [IM]). Statistical analyses were performed using the Mann-Whitney U test. Progression-free survival (PFS) and overall survival (OS) were analyzed using the Kaplan-Meier method. Cox proportional hazard regression was used for univariate and multivariate analyses. Results: The median follow-up for all patients who were alive at the last follow-up was 33.5 months (range, 1–104 months). The PFS and OS rates were worse for patients with at least 15.0% than for those with less than 15.0% loss of skeletal muscle and IM from baseline ( P < 0.001 for both). Furthermore, multivariate analyses showed that at least 15.0% loss of IM was an independent prognostic factor for PFS and OS ( P = 0.002 for both). Conclusions: Sarcopenia (≥15.0% loss of IM from baseline) was revealed to be an important prognostic factor in patients with CC undergoing CCRT.